Permissible and immunogenic HLA-A mismatches: Cytotoxic T cell precursor frequencies reflect graft survival data - Roelen, D; Stobbe, I; Young, N; Van Bree, F; Doxiadis, I; Oudshoorn, M; Morris, P; Wood, K; Claas, F (2001)
By analysis of the immunogenicity of single HLA mismatches in the context of the patients own HLA phenotype, Maruya et al. were able to define permissible and immunogenic HLA mismatches. Kidney graft survival in case of permissible mismatches was similar to that of completely HLA matched combinations whereas immunogenic mismatches lead to a significantly poorer graft survival. In the present study we tested whether the permissible and immunogenic nature of HLA mismatches is also reflected in the Cytotoxic T Lymphocytes (CTLs) allorepertoire in vitro. Limiting dilution experiments were performed to analyse the number of precursor CTL directed against individual HLA class I antigens. In general, the frequency of CTLp directed against permissible HLA-A antigens (n=70, mean frequency 27 CTLp per million PBLs) was found to be significantly lower compared to the CTLp directed against immunogenic HLA-A antigens (n=73, mean frequency 59 CTLp per million PBLs). This difference was found in healthy individuals and in a population of renal transplant candidates. Furthermore, these data were confirmed by a retrospective analysis of CTLp frequencies performed between partly mismatched unrelated bone marrow donors and their potential recipients. We conclude that on the population level the permissible and immunogenic HLA-A mismatches are indeed reflected in the CTL allorepertoire. However, due to the big overlap of the CTLp frequencies in these populations, the permissible or immunogenic nature of a mismatch should be determined on an individual basis. © 2001 Blackwell Science Ltd,.